Influence knowledge Management and talent Managementon Employee Performance Withemployee Engagementas an Intervening Variable in the Youth and Sports Service of West Sumatra Province - Okta Meridiana; John Veri (Jurnal Multidisiplin Sahombu, 2025)
This study aims to examine the influence of knowledge management and talent management on employee performance, with employee engagement as an intervening variable, at the West Sumatra Provincial Youth and Sports Office. Data collection was conducted through a survey and questionnaire distribution, with a sample of 78 respondents. The analysis method used was structural equation modeling using SmartPLS. The research results obtained Knowledge management has a positive and significant effect on employee engagement. Talent management has a positive and significant effect on employee engagement. Knowledge management has a positive and significant effect on employee engagement on employee performance. Talent management has a positive and significant effect on employee engagement on employee performance. Employee engagement has a positive and significant effect on employee engagement on employee performance. Employee engagement mediates the effect of knowledge management on employee performance. Employee engagement mediates the effect of talent management on employee performance.